The Principal’s Transformational Leadership Style and Its Impact on Elementary School Teachers’ Performance - Tarno; Jufri (Institute Journal and Publication Muhammadiyah University of Buton, 2025)
This study examines the principal’s transformational leadership and its impact on teacher performance in an elementary school context through a case study at SDN 1 Buton. The study is grounded in the need for elementary schools to improve instructional quality and strengthen teachers’ work culture amid policy changes, the reinforcement of literacy and numeracy, and increasing accountability in educational services. The research aims to describe the principal’s transformational leadership practices based on the dimensions of idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration, and to analyze their implications for teacher performance in lesson planning, instructional implementation, assessment practices, classroom management, and professional development. A qualitative approach with a case study design was employed. Data were collected through in depth interviews with the principal and teachers, observations of school and classroom activities, and document analysis (school programs, instructional plans, supervision notes, and teaching administration). Data were analyzed thematically through iterative processes of reduction, categorization, and conclusion drawing, with source and method triangulation to enhance credibility. The findings indicate that transformational leadership builds teachers’ trust and collective commitment through role modeling and policy consistency; enhances work motivation through a clear vision and recognition; encourages gradual innovation through reflective practices and sharing forums; and strengthens psychological safety through coaching-oriented supervision. These practices were associated with more structured instructional documents, more active and responsive teaching, more consistent formative assessment and follow up, and more orderly classroom management. Key constraints included administrative workload, varying levels of digital readiness, limited resources, and student heterogeneity. The study recommends streamlining administrative demands, strengthening teacher professional learning communities, and improving resource support to sustain performance gains.